Comparative emissions characterization of a small-scale wood chip-fired boiler and an oil-fired boiler in a school setting. (December 2017) - Rector, Lisa; Miller, Paul J.; Snook, Steven; Ahmadi, Mahdi
Abstract: To investigate the differences in emissions performance between wood chip and oil-fired boilers under real-world operating conditions, a series of stack tests were performed to measure air pollutant emissions at a wood chip stoker boiler with multi-cyclone emission controls. This type of wood combustion boiler technology (inclined grate stoker boiler with a heat input rating between 880 and 4700 kW) represents the largest number of installations in the northeastern United States. The monitored air pollutant stack emissions from the wood chip boiler were compared to those from an oil-fired boiler used as backup at the same location. The stack test results found that total particulate matter emissions from the wood-fired boiler with a multi-cyclone emission control device were almost 30 times higher on a mass per energy input basis than the oil-fired boiler burning No. 2 distillate oil with 2.2 g kg −1 sulfur content under similar real-world operating conditions. Highlights: Wood chip boilers tested under high-load, steady-state conditions may underrepresent typical use air pollutant emissions. A wood chip boiler had total particulate emissions 30 times higher than a co-located distillate fuel oil boiler. Installing wood chip boilers lacking advanced controls can result in higher particulate levels relative to distillate oil.